The platform economy in Europe: Results from the second ETUI Internet and Platform Work Survey - Agnieszka Piasna; Wouter Zwysen; Jan Drahokoupil (European Trade Union Institute (ETUI), 2022)
This paper presents some of the key insights from the second wave of the ETUI Internet and Platform Work Survey (ETUI IPWS) conducted in 14 member states of the European Union (EU) in Spring 2021. The use of standard probability sampling allows us to estimate the proportion of internet and platform workers, and to identify their characteristics, in a way that is generalisable to the working age population. We found the prevalence of internet and platform work to be relatively similar in the analysed countries, suggesting a uniform evolution of this type of work across the EU. In particular, 17% of the working age population did some internet work in the past year, 4,3% did platform work and 1,1% can be classified as 'main platform workers'; that is, working 20 hours or more per week or earning more than 50% of their income through platforms. Internet and platform workers differ from the offline workforce in several ways. They tend to be somewhat younger but are far from constituting a student workforce. They are better educated than those who have never done internet work and this is particularly the case for higher skill professional work. Internet work seems mainly to complement offline precarious work and serves as an extra source of income for those on less stable contracts.
Keywords: 330; Netzwerkökonomik; Gig Economy; Atypische Beschäftigung; EU-Staaten